2017
DOI: 10.1136/archdischild-2016-311959
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal ethanol exposure from ethanol-based hand sanitisers in isolettes

Abstract: Preterm neonates in the isolette are at risk of inadvertent exposure to ethanol. The expected blood alcohol level from this exposure is small and below 1 mg/dL level recommended by European Medicines Agency to limit the ethanol exposure in children. The unintended ethanol exposure can be avoided by rubbing hands for at least 20 s after applying EBHS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…The antifungal complex showing synergism at 22°C (room temperature) can be utilized in health care centers, pharmaceutical and medical industries for the prevention of cutaneous candidiasis. Conventional chemical agents used in cleansers or antiseptic cause skin irritation, such as dryness, and are harmful to infants and children, who have less developed immune systems than those of adults (48)(49)(50)(51). The antifungal complex can be utilized as novel surfacesanitizer in facilities such as animal farms where the occurrence of fungal contamination is higher with livestock and commercial sanitizers, such as sodium hypochlorite, have little antimicrobial effects (52,53).…”
Section: Discussionmentioning
confidence: 99%
“…The antifungal complex showing synergism at 22°C (room temperature) can be utilized in health care centers, pharmaceutical and medical industries for the prevention of cutaneous candidiasis. Conventional chemical agents used in cleansers or antiseptic cause skin irritation, such as dryness, and are harmful to infants and children, who have less developed immune systems than those of adults (48)(49)(50)(51). The antifungal complex can be utilized as novel surfacesanitizer in facilities such as animal farms where the occurrence of fungal contamination is higher with livestock and commercial sanitizers, such as sodium hypochlorite, have little antimicrobial effects (52,53).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ethanol is among the excipients contained in medications that are administered to very low birth weight neonates leading to significant exposure during a critical period of neuronal circuit refinement (Akinmboni et al, 2018). Sanitizers used before inserting hands into isolette incubators can also release enough alcohol vapor to produce significant exposure in premature babies (Hsieh et al, 2018). A large body of experimental evidence indicates that ethanol use during late pregnancy can have striking effects on child behavior, particularly when consumed in a binge-like manner (Niclasen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, 3-pentanone (1/K0 = 0.546 Vs/cm 2 ; RT = 7.4 s) and acetone (1/K0 = 0.544 Vs/cm 2 , RT = 2.4 s) both eluate in the proximity of ethanol (1/K0 = 0.510 Vs/cm 2 , RT = 0.0 s) and therefore might be hidden at high ethanol concentrations. Hsieh et al (27) demonstrated that the ethanol concentration in neonatal incubators remained in a concentration of up to 5 ppm v 30 min after the use of hand sanitizers. Ulanowska et al (28) reported a calibration range for MCC/IMS of ethanol in the ppb v range, which is approximately 1/100–1/1,000 of the expected concentration according to Hsieh et al (27).…”
Section: Discussionmentioning
confidence: 99%
“…Hsieh et al (27) demonstrated that the ethanol concentration in neonatal incubators remained in a concentration of up to 5 ppm v 30 min after the use of hand sanitizers. Ulanowska et al (28) reported a calibration range for MCC/IMS of ethanol in the ppb v range, which is approximately 1/100–1/1,000 of the expected concentration according to Hsieh et al (27).…”
Section: Discussionmentioning
confidence: 99%